The Impact of Minimarket Expansion on the Income of Traditional Retail Shops in Mahato Village, North Tambusai District, Rokan Hulu Regency - Siti Rohimah Siregar; Hansen Rusliani (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Retail modernization has expanded consumer choice while increasing competitive pressure on traditional neighborhood shops, particularly in rural communities where small-scale retail remains closely connected to household livelihoods. However, the effects of minimarket expansion on rural retailers and their adaptive responses remain insufficiently understood. This study examined the effects of minimarket expansion on the income of traditional retail shops in Mahato Village, North Tambusai District, Rokan Hulu Regency, and identified the strategies adopted by shop owners in response. A descriptive qualitative case study was conducted with five shop owners purposively selected according to business duration, location, and proximity to minimarkets. Data were collected through interviews, observations, and documentation and analyzed through data reduction, data display, interpretation, and conclusion drawing. All five shop owners reported monthly income declines ranging from 20% to 34.29%, accompanied by reductions in customer numbers. Consumers’ shift toward minimarkets was associated with shopping convenience, greater product variety, price certainty, and promotional offers. In response, traditional shop owners expanded their product assortments, improved store layouts, extended operating hours, maintained informal credit arrangements, offered small discounts, and strengthened personalized service. The findings indicate that the sustainability of traditional retail shops depends not only on business adaptation but also on their ability to leverage social trust, relational proximity, and service flexibility. This study contributes context-specific evidence on rural retail competition and highlights the need for policies that support the adaptive capacity and sustainability of small-scale retailers.